Taking the narrow way: Lovering, evil, and knowing what God would do - Rhodes, Ryan E. (International journal for philosophy of religion, 2015)
Theists are, according to Lovering, in an 'unenviable position.' Lovering (, 104). Noting that debates on evil and God's existence depend conceptually upon claims about what God would or would not do, he lays out three frameworks within which such claims could operate, all of which raise significant problems for theism. While his contention that these arguments depend on such claims is correct, the dire consequences for theism do not follow. After briefly discussing his three alternatives, I will argue that while some of his supporting arguments are successful, his overall conclusion is not. Although both Broad Skeptical Theism and Broad Epistemic Theism are untenable, the latter has more resources than he suggests for dealing with the evidential argument from evil. More significantly, Narrow Skeptical Theism need not be ad hoc as Lovering contends, but is a position which we ought to accept provided it is not itself used as a pseudo-theodicy. The upshot of these observations is that theistic arguments may reasonably be grounded in considerations about what God would do.